Prevalence and Predictors of Diabetic Retinopathy: A Community-Based Study in North India Among Type 2 Diabetes Patients - Zubair, Mohd Yasir; Ansari, Mohammad Athar; Siddiqui, Ziya; Mehnaz, Saira; Khalil, Salman (National Journal of Community Medicine, 2025)
Background: Between 1970-1975, DR was the 20th cause of blindness, and today, it is the 6th most common cause of blindness in India. This study aimed to estimate the prevalence of DR among type 2 diabetes patients and identify associated socio-demographic determinants. Methods: Total of 316 type 2 diabetics patients through systematic random sampling were enrolled. Fundus examination was performed using Volk iNview iPhone fundus camera following ETDRS protocol. Data on demographics, anthropometric measurements, and clinical parameters were collected. Statistical analysis included chi-square tests and logistic regression to identify the risk factors. Results: Prevalence of any grade of DR was 35.4% (95% CI: 30%-41.5%) which included mild non-proliferative (15.5%), moderate non-proliferative (11.7%), severe non-proliferative (3.8%), proliferative (1.6%), and diabetic macular edema (2.8%). Multivariate analysis identified significant independent risk factors: age >60 years (adjusted OR=1.11), diabetes duration >5 years (adjusted OR=1.20), uncontrolled glycemia (adjusted OR=2.25), hypertension (adjusted OR=1.04), previous cataract surgery (adjusted OR=1.76), and overweight/obesity (adjusted OR=1.202). Conclusion: Predominance of early-stage disease highlights the opportunity for early intervention through community-based screening initiatives. The findings emphasize the importance of integrated diabetes management addressing multiple risk domains, particularly glycemic control, blood pressure management, and weight optimization, for effective DR prevention and management.